PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 4 MANIAMOLO - Resmi Murni Zagoto (Universitas Nias Raya, 2026)
The aim of this research is to find out how learning motivation influences the mathematics learning outcomes of class VIII students at SMP Negeri 4 Maniamolo throughout the 2023–2024 academic year. Ex-post facto investigations and quantitative approaches were used in this research methodology. The research population was fifty-five children from two classes in grade VIII. Simple random sampling is the sampling technique used in this research. Class VIII-A students were used as the research sample. Tests and questionnaires were used to collect data, and basic linear regression analysis was used to analyze the results. The calculation results show that the desire to learn has a significant effect on learning outcomes, rejecting H0 and accepting Ha, with a significance value of 0.000 < 0.05 and t count > t table (9.426 > 1.703). An influence of 76.7% is shown by the coefficient of determination or R Square value of 0.767. This shows that there is a correlation of 76.7% between the independent variable (desire to learn) and the dependent variable (learning outcomes).